Effect of Phosphate Solubilizing Bacteria and Phosphorus Sources on Soil Phosphorus Availability and Maize Yield - Ojha, Aanchal; Gairhe, Janma Jaya; Tripathi, Bhaba Prasad; Ojha, Roshan Babu; Pokhrel, Sarad (Journal of Agriculture and Forestry University, 2026)
Phosphorus is an important nutrient for maize; however, its availability in soil may be restricted due to binding to clay surfaces and precipitation with cations such as aluminium and iron at low pH and calcium and magnesium at high pH, ultimately affecting maize growth, development and yield. Phosphate solubilizing bacteria helps to improve soil phosphorus availability by transforming insoluble phosphorus to plant-available forms, thereby supporting improved crop growth and yield. To address this, a field experiment was conducted in Taukhel, Lalitpur, Nepal following a split-plot design with phosphate solubilizing bacteria inoculation and noninoculation as the main plot factor and five phosphorus sources: control, rock phosphate, single super phosphate, bone meal and poultry manure as sub-plot factors, each replicated three times. Results showed no significant interaction between phosphate solubilizing bacteria and phosphorus sources. However, inoculation of phosphate solubilizing bacteria significantly increased thousand grain weight, grain yield, stover yield and soil available phosphorus by 2.1%, 11.6%, 9.7% and 13.4% respectively, compared with no inoculation. Similarly, among phosphorus sources, plots treated with poultry manure improved plant height, number of leaves, ear length, number of kernels per row, thousand grain weight, grain yield, stover yield and soil available phosphorus by 14.6%, 14.9%, 19.5%, 16.6%, 7.3%, 34.2%, 26.3% and 46.1% respectively, compared to control. The results of our study suggests that maize seed inoculation with phosphate solubilizing bacteria improved maize yield and soil available phosphorus in comparison to non-inoculated treatments. However, additional research is essential to understand combined effects of phosphate solubilizing bacteria with organic and inorganic fertilizers on soil nutrient availability and crop productivity.